Advances in the chemistry of base-stabilized germanium(I) compounds towards C-C bond formation - Ong, Melissa Xin Yi (Nanyang Technological University, 2020)
The synthesis of base-stabilized germanium(I) dimers and a silagermyne were reported. In addition, the application of the base-stabilized germanium(I) dimers toward catalytic C-C bond formation of α,β-unsaturated carbonyl compounds was described. In Chapter 1, a brief introduction of low-valent heavier group 14 element carbene analogues and multiple bonded heavier group 14 element compounds was described. The small energy difference between the HOMO and LUMO facilitates their capability of transition-metal like reactivity in small molecules activation. In Chapter 2, the synthesis of base-stabilized germanium(I) dimers and their application toward C-C bond formation of α,β-unsaturated carbonyl compounds was reported. First, treatment of the amidinate-stabilized chlorogermylene and the 2-imino-5,6-methylenedioxylphenyl chlorogermylene with potassium graphite (KC8) afforded the amidinato germanium(I) dimer [RGeGeR] and the 2-imino-5,6-methylenedioxylphenyl germanium(I) dimer [LGeGeL] respectively. With the base-stabilized germanium(I) dimers in hand, they were used to investigate C-C bond formation reactions through the polymerization of various α,β-unsaturated carbonyl compounds to form corresponding polymers with low molecular weight and low dispersity. The successful polymerization led us to investigate and propose the mechanism of polymerization in a traditional initiation-propagation-termination manner. In chapter 3, we showed the synthesis of the base-stabilized unsymmetric silagermyne [LGeSiR]. The in-situ generation of LGeK was when the 2-imino-5,6-methylenedioxylphenyl chlorogermylene was treated with excess potassium graphite. The silagermyne was afforded from the reaction of LGeK with the amidinato chlorosilylene [RSiCl]. We then investigated the reactivity of LGeSiR with various Lewis acids, chalcogens and transition metal carbonyls, of which the successful isolation of the [LGe-Te-Si(Te)R] complex was reported by X-ray crystallography. Additionally, we attempted to mimic a push-pull NHC-disilyne-ZnCl2 with LGeSiR but instead of forming the push-pull complex, we formed a [LH]-GeCl2 dimer isolable by X-ray crystallography.